2023
DOI: 10.1001/jamanetworkopen.2023.36400
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Antiobesity Drugs for Adolescents With Severe Obesity

Shweta Mital,
Hai V. Nguyen

Abstract: ImportanceAlthough the American Academy of Pediatrics has recommended treatment with antiobesity drugs for adolescents, the cost-effectiveness of antiobesity drugs for this population is still unknown.ObjectiveTo quantify cost-effectiveness of different antiobesity drugs available for pediatric use.Design, Setting, and ParticipantsThis economic evaluation used a Markov microsimulation model with health states defined by obesity levels. Effectiveness was measured by quality-adjusted life-years (QALYs) and costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Based on the current studies inclusion dates, and eligibility criteria, there were no studies assessing the cost‐effectiveness of obesity pharmacotherapy in this age group highlighting the need for additional investigation of individual level cost‐effectiveness analysis for obesity pharmacotherapy in youth 46 . However, recently, there were two studies published that reported the cost‐effectiveness of obesity pharmacotherapy in adolescents utilizing Markov microsimulation models with costs estimated from the health system perspective 47,48 . While these studies did not include individual level data, given the recent and pending regulatory approvals for multiple highly effective pharmacotherapies, such as the glucagon‐like‐1‐peptide agonist, the results were highly pertinent to the field of paediatric obesity medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the current studies inclusion dates, and eligibility criteria, there were no studies assessing the cost‐effectiveness of obesity pharmacotherapy in this age group highlighting the need for additional investigation of individual level cost‐effectiveness analysis for obesity pharmacotherapy in youth 46 . However, recently, there were two studies published that reported the cost‐effectiveness of obesity pharmacotherapy in adolescents utilizing Markov microsimulation models with costs estimated from the health system perspective 47,48 . While these studies did not include individual level data, given the recent and pending regulatory approvals for multiple highly effective pharmacotherapies, such as the glucagon‐like‐1‐peptide agonist, the results were highly pertinent to the field of paediatric obesity medicine.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies did not include individual level data, given the recent and pending regulatory approvals for multiple highly effective pharmacotherapies, such as the glucagon‐like‐1‐peptide agonist, the results were highly pertinent to the field of paediatric obesity medicine. The economic evaluation completed by Mital et al suggested that the phentermine‐topiramate combination agent was the most cost‐effective of all the available FDA approved medication for paediatric obesity due to the high cost of semaglutide despite it being more effective than phentermine‐topiramate in terms of weight loss 48 . Lim et al found that in an economic evaluation of 100,000 simulated adolescents with obesity, no obesity pharmacotherapy was cost effective after 2 years, however high dose phentermine‐topiramate was projected to be cost‐effective after 5‐years with an ICER of USD 56,876 per QALY gained 47 …”
Section: Discussionmentioning
confidence: 99%
“…Mital and Nguyen used a Markov microsimulation model to perform an economic evaluation and determine the incremental cost-effectiveness ratio (ICER) of the four antiobesity drugs with current FDA approval for pediatric use (semaglutide, phentermine-topiramate, liraglutide, orlistat), with effectiveness measured using quality-adjusted life-years (QALYs) over a 10-year horizon. They found that although semaglutide led to more QALYs than phentermine-topiramate, due to semaglutide's high cost, phentermine-topiramate was most cost-effective (semaglutide ICER = $1079,480 per QALY and phentermine-topiramate ICER = $93 620 per QALY, vs. no treatment, for 12–17-year-old adolescents with severe obesity) [40 ▪▪ ]. In a similar economic evaluation, Lim and colleagues estimated the cost-effectiveness of semaglutide, mid- and top-dose phentermine-topiramate, and liraglutide, as an adjunct to lifestyle counseling vs. lifestyle counseling alone for adolescents with obesity.…”
Section: Limitations To Widespread Usementioning
confidence: 99%
“…In real-world settings, many patients continue GLP-1 therapy, with weight loss plateauing while drug costs continue. Two recent analyses, not funded by the manufacturer, calculated incremental costs per QALY for semaglutide of $351 000 to $508 000 for adults and more than $1 million for adolescents with obesity . All of these analyses accounted for multiple downstream complications of obesity and likely overestimate cost-effectiveness, given lower weight loss achieved in real-world settings compared with the trials…”
mentioning
confidence: 99%